Transitioning through the vapour-liquid equilibrium for low energy thermal stripping of ammonia from wastewater: enabling transformation of NH3 into a zero-carbon fuel - Luqmani, Benjamin A.; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Pidou, Marc; McAdam, Ewan (Elsevier, 2024)
Vacuum thermal stripping permits the recovery of ammonia from wastewater in a concentrated form, which is key to its exploitation in the circular economy, but the latent heat demand for thermal separation remains a critical barrier to exploitation. In this study, we investigate the vapor-liquid equilibrium (VLE) for ammonia-water as a mechanism to enhance recovered ammonia quality and minimise the thermal energy required for ammonia separation. Below the dew point (65 °C at 0.25 bar) a two-phase region of the VLE exists where 48 %wt gas-phase ammonia could be produced (61 °C) compared to only 2 %wt within the stripping region adopted widely in the literature. This was complemented by a 98 % reduction in thermal separation energy, since limited water vaporization can occur when the feed is maintained below the activation energy threshold for bulk evaporation. Operation within this practically unexplored region of the ammonia-water VLE fosters a gas-phase product suitable for energy generation in gas turbines or solid oxide fuel cells. Comparable product quality was achieved using concentrated wastewater, which validated the VLE for design in the presence of a broad range of dissolved gases and volatile inorganic compounds. Rapid desorption of CO2 occurred during vacuum stripping, subsequently increasing pH >9 without the requirement for alkali addition to shift the ammonia-ammonium equilibrium in favor of gaseous ammonia. Consequently, the two-phase region of the VLE defined for vacuum thermal stripping provides a synergistic strategy to mitigate chemical demand, minimise separation energy and recover gas-phase ammonia for zero carbon energy generation, constituting a significant advancement toward the net zero ambitions of the water sector.
Keywords: Ammonia to energy; Vacuum stripping; Net zero; Resource recovery; Wastewater